2008
DOI: 10.1002/sce.20330
|View full text |Cite
|
Sign up to set email alerts
|

Alignment between the physics content standard and the standardized test: A comparison among the United States‐New York State, Singapore, and China‐Jiangsu

Abstract: Alignment between content standards and standardized tests is a significant issue to society, science pedagogy, and test validation. To better understand the issues related to alignment, this study compares the alignment in physics among three education systems: Jiangsu (China), New York State (United States), and Singapore. The same coding framework for content standards and standardized tests is used to compute the alignment indices in the three education systems. It was found that there was a statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 22 publications
2
42
1
Order By: Relevance
“…As was shown with the comparison of alignments among Chinese and New York State physics (Liu et al, 2009), some observed alignments were clearly lower than the mean at the .05 level, whereas others were significantly above the mean. Additionally, Liu and Fulmer (2008) showed that alignment between a test and the relevant curriculum may change with different testing instances, with some test forms being better aligned than others.…”
Section: Discussionmentioning
confidence: 75%
“…As was shown with the comparison of alignments among Chinese and New York State physics (Liu et al, 2009), some observed alignments were clearly lower than the mean at the .05 level, whereas others were significantly above the mean. Additionally, Liu and Fulmer (2008) showed that alignment between a test and the relevant curriculum may change with different testing instances, with some test forms being better aligned than others.…”
Section: Discussionmentioning
confidence: 75%
“…These representations have been widely used in mathematics, although thus far only in the area of high-school physics (Liu et al, 2009). They seem promising for curriculum research and will thus be introduced to readers in this journal.…”
Section: Inter-rater Reliabilities and Methodological Decisions For Cmentioning
confidence: 98%
“…The other five common subject areas generally experienced minimal divergences of 0.00-0.05 (i.e. 0%-5% in the blue regions) (see Liu et al, 2009 for details on these calculations). The Porter Alingment Index was calculated to be 0.71, which means that the degree of alignment for both countries in these six groupings along their cognitive dimensions was high (Porter, 2006).…”
Section: 23mentioning
confidence: 99%
“…Alignment has seen slight change in definition since the 1940s, with a consistent focus on the concept of “agreement,” and a variety of source materials being compared on extent of agreement: instruction and curriculum (Tyler, ); content across grades (Wise & Alt, ); institution‐wide or school‐improvement targets (Pautler, 1989; Scott, ); and intended learning outcomes and expectations (La Marca, Redfield, Winter, & Despriet, ). Alignment work from the late 1990s and into the 2000s as part of the standards‐based reform movements, with the related attention to accountability measures, examined tests’ alignment with standards (Liu et al, ; Porter, ), and the test validity implications of alignment (Beck, ), while later worked turned to comparisons of standards across states and patterns of teachers’ reported practice (Polikoff & Porter, ).…”
Section: Alignment Definitions and Methodsmentioning
confidence: 99%
“…In some cases, this means that a single overarching objective could be broken into multiple subobjectives (see Polikoff, , p. 1194, for a detailed example). For tests, the questions are typically segmented according to each standalone item (Liu & Fulmer, ; Liu et al, ). For many question formats, such as multiple choice, true‐false, or short answer, this would be the entire question.…”
Section: Alignment Definitions and Methodsmentioning
confidence: 99%